MARs Wars: heterogeneity and clustering of DNA-binding domains in the nuclear matrix - Vassetzky, Y.S.; Ioudinkova, E.S.; Razin, S.V. (Вiopolymers and Cell, 2009)
Aim. CO326 is a chicken nuclear scaffold/matrix attachment region (MAR) associated with the nuclear matrix in several types of chicken cells. It contains a binding site for a sequence-specific DNA-binding protein, F326. We have studied its interaction with the nuclear matrix. Methods. We have used an in vitro MAR assay with isolated matrices from chicken HD3 cells. Results. We have found that an oligonucleotide binding site for the F326 inhibits binding of the CO326 to the nuclear matrix. At the same time, the binding of heterologous MARs is enhanced. Conclusions. Taken together, these data suggest that there exist several classes of MARs and MAR-binding domains and that the MAR-binding proteins may be clustered in the nuclear matrix. Мета. CO326, ділянка прикріплення до ядерного матриксу, містить сайт звязування з ДНК-звязувальним білком F326. Методи. Для аналізу матриксу, виділеного з клітинної лінії HD3, використано in vitro MAR-метод. Результати. Олігонуклеотид, який містить сайт звязування білка F326, інгібує звязування CO326 з ядерним матриксом, при цьому асоціація гетерологічних ділянок прикріплення до ядерного матриксу зростає. Висновки. Одержані дані свідчать про те, що різні ДНК-звязувальні білки утворюють кластери у ядерному матриксі Цель. CO326, участок прикрепления к ядерному матриксу, содержит сайт связывания с ДНК-связывающим белком F326. Методы. Для анализа матрикса, выделенного из клеточной линии HD3, использован in vitro MAR-метод. Результаты. Олигонуклеотид, содержащий сайт связывания белка F326, ингибирует связывание CO326 с ядерным матриксом, при этом ассоциация гетерологичных участков прикрепления к ядерному матриксу увеличивается. Выводы. Полученыые данные свидетельствуют о том, что различные ДНК-связывающие белки образуют кластеры в ядерном матриксе.